2022
DOI: 10.1093/ofid/ofac503
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Vaccination Decreases COVID-19-Associated Morbidity and Mortality Among Organ Transplant Recipients: A Contemporary Cohort Study

Abstract: Background Organ transplant recipients (OTR) are less protected from vaccination than immunocompetent hosts. Additional vaccine doses have shown increased immunogenicity. Few studies assessed their clinical efficacy, particularly against Omicron variants, since most included patients from earlier phases of the pandemic, with higher base mortality rates. Methods We studied adult OTR who had COVID-19 between 12/15/21 and 5/25/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…4 ), despite concerns for lower immunological vaccine efficacy among immunocompromised patients [ 16 , 17 ], and one small study from the CCC19 registry, which showed comparable clinical outcomes between unvaccinated patients with cancer and those who had received 2 doses of an mRNA vaccine [ 19 ]. The results of the present report are consistent with those of a previously published study at our center among organ transplant recipients [ 27 ], and the updated CCC19 data [ 18 ], highlighting that vaccination of immunocompromised patients, especially with additional “booster” doses, is an essential preventive strategy against severe COVID-19 and death.…”
Section: Discussionsupporting
confidence: 91%
“…4 ), despite concerns for lower immunological vaccine efficacy among immunocompromised patients [ 16 , 17 ], and one small study from the CCC19 registry, which showed comparable clinical outcomes between unvaccinated patients with cancer and those who had received 2 doses of an mRNA vaccine [ 19 ]. The results of the present report are consistent with those of a previously published study at our center among organ transplant recipients [ 27 ], and the updated CCC19 data [ 18 ], highlighting that vaccination of immunocompromised patients, especially with additional “booster” doses, is an essential preventive strategy against severe COVID-19 and death.…”
Section: Discussionsupporting
confidence: 91%
“…This is specially the case for organ-transplanted patients or patients suffering multiple sclerosis. These patients did not benefit from BNT162b2 and mRNA-1273 vaccines due to their immunosuppressive treatments [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. On the other hand, the efficacy of these vaccines has been demonstrated in patients with several types of cancers.…”
Section: Advantages and Caveats Of Efficacy And Safety Of Mrna Sars-c...mentioning
confidence: 99%
“…Second, Johnson et al reference as positive studies that, in fact, contradict potential therapeutic benefits of molnupiravir. Lastly, vaccination status is a major confounder [ 1 , 2 , 4 , 5 ].…”
mentioning
confidence: 99%
“…On the contrary, sotrovimab outperformed the no-intervention group, having lower hospitalization or death rates ( p = 0.045) [ 2 ]. It should be noted that, in the study by Radcliff et al 68% of patients (30/49) in the molnupiravir group had received at least three doses of mRNA vaccine or two doses of the Ad26.COV2.S vaccine, compared to 38% (18/48, χ 2 p = 0.019) of the no-intervention group, which could on its own have explained the difference in outcomes [ 2 , 4 ]. Johnson et al summarize the findings of this study without mentioning this important caveat.…”
mentioning
confidence: 99%
See 1 more Smart Citation